An amperometric needle-type glucose sensor tested in rats and man. - Matthews, DR; Bown, E; Beck, T; Plotkin, E; Lock, L; Gosden, E; Wickham, M (1988)
An amperometric glucose-measuring 25 gauge (0.5 mm diameter) needle-type sensor has been developed using a glucose oxidase and dimethyl ferrocene paste behind a semi-permeable membrane situated over a window in the needle. Electron transfer results in direct current generation. Sensors have been tested subcutaneously in the abdomen both in anaesthetized rats (40 sensors, 11 rats) and in normal, conscious man (20 sensors, 10 subjects). In rats the blood glucose was modulated by glucose and by insulin infusion. In man the glucose concentrations were rapidly changed by use of a glucose clamp at 12 mmol/l plasma concentration for 2 h, after which the glucose returned to normal. In rats the median correlation between glucose change was 0.83 with an interquartile range from 0.70 to 0.92, and in man the median correlation was 0.80 with an interquartile range 0.67 to 0.86. Hysteresis, a measure of the accuracy on the upswing and downswing, was not a problem and cross-correlation showed no phase-lag. There were quantitative differences between in vitro calibration and the performance in vivo, reflecting the different conditions of use. The current in response to a glucose concentration was stable over 6.0 h in rats and 4.5 h in man.